Case study: Wisma Am First, Kelana Jaya - Muhammed Hadli, Amirul Hazeem; Mohammad Asri, Muhammad Raziq; Agustan, Akid Aiman; Mohd Sab, Johan Muqris (2024)
We have interpreted every action we took throughout our case study at the Wisma Am First in Kelana Jaya in this report. The primary emphasis of this case study is the way the building maintenance department oversees and manages building maintenance. This report's content is comprised of all the data we obtained from the maintenance department and the building in accordance with the work specifications. We provide the property, organisational, and maintenance management aspects of the building in accordance with the requirements. Next are the planning, building design, technology, and maintenance policy. In addition, the case study's legal component, maintenance plan, and building condition evaluation. Comprising the budget for finances and upkeep as well as the issues and analysis of recommendations. All of the information provided by the maintenance department for our case study is included in this report.From the perspective of the students, this case study explains the building's maintenance management. Updating the building's exterior, minimising discomfort, and guaranteeing occupant safety can all be seen as critical aspects of maintaining the property's long-term value. We sincerely hope that the report's disclosed general contents will satisfy all readers and provide a wealth of knowledge.